A note on the post-structuralist evolution of discourse analysis (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
This paper gives a critical overview of various analytical approaches dominating the field of discourse studies in the last three decades, from the perspective of their philosophical and formative bases: social constructionism and linguistics. It explores different conceptions and features of the theoretical nexus between these two bases leading to the emergence of three distinct yet apparently complementary strands of thought (i-iii). The paper starts with the account of (i) Laclau and Mouffe’s classical discourse theory and its idea of ‘discursive struggle’ – a struggle of particular ways of talking of and understanding the world in an attempt to achieve discursive (and social) hegemony. Laclau and Mouffe’s assumption that no discourse is a closed entity but rather transformed through contact with other discourses is then taken as the introductory premise to present a vast, complex and heterogeneous family of (ii) critical discourse studies. Critical discourse studies are characterized in the paper as a hub of text-analytical practices that work on the link between language and social reality from the perspective of power and empowerment, explaining how discourse partakes in the production, change and negotiations of ideologically-charged meanings. Most crucially, they establish a methodological link between social theory and linguistics, providing discourse analysis with text-analytical tools and methods. Finally, the paper discusses (iii) three recent discourse analytical models: Discourse Space Theory, Critical Metaphor Analysis and Legitimization-Proximization Model. Originally located in the cognitive-psychological strand of critical discourse studies, these new models can now be seen as fully-fledged discourse theories with their own apparatus of analysis, involving concepts from cognitive linguistics, pragmatics and social psychology. It is argued that these three new theories make a further (and thus far final) step toward consolidation of the social-theoretical and linguistic bases in contemporary discourse studies. The empirical benefits of this consolidation are discussed in the last part of the paper, which includes a brief case study where the new models are used in the analysis of Polish anti-immigration discourse.